Study on the Stochastic Model for Excessive Air Conditioning Use in Japanese Dwellings - Imagawa, Hikaru; Rijal, Hom Bahadur; Shukuya, Masanori (Journal of the Institute of Engineering, 2020)
Thermal adjustment is one of the most important behaviours. In daily life, we use some behavioural adjustments. It is not always obtained the optimal condition by the thermal adjustments. For example, it happens to use excessive air conditioning for thermal adjustments. Especially, the excessive air conditioning use is important issue not only for the human comfort but also for the energy use. The occupant behaviour stochastic model was proposed by some previous researches around the world. However, these models show only the state of the occupant behaviour, and thus the excessive adjustments are not known. The objective of this research is to clarify quantitatively the excessive thermal adjustments which are happened to be in the stochastic model. The thermal measurement and occupant behaviour survey was conducted in 120 dwellings during 4 years period in Kanto region of Japan. The number of samples collected was 36,114. We analysed the occupant behaviour stochastic model of the excessive cooling and heating use. The thermal sensation vote (TSV) and the thermal preference vote (TP) were used to classify the excessive air conditioning use. The proportion of excessive cooling use were increased when outdoor air temperature was increased. In addition, there were no significant difference between TSV and TP for calculating the proportion of the excessive air conditioning use in Japanese dwellings. These models are useful to understand the possibility of the energy saving. In the future, the model will be implemented in the building thermal simulation to predict the energy use in building.